Sobre los orígenes de las caballerías en Castilla y León. Siglos X-XII - Astarita, Carlos (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2007)
In the process of constitution of medieval knighthood it is inevitable to speak of the formation of a class of power, and the structuring of feudalism. But this perspective reveals its insufficiency in the particular case of Castile and Leon, for which two differentiated estates must be considered: infanzones, assimilated to the last scale of the feudal class and the caballeros villanos ('rural knights'), without power of ban of their own, or personal bonds of vasallage. The principle that enrichment was the basis of power is contested by another one, which we will explore in this contribution, that emphasizes the mechanisms of political subordination of the peasants to explain the genesis of this system. The evolutions were carried out with a singular chronology for each district, a vision quite different from the one presented by authors who stated the so called "feudal mutation" (a synchronic change in a whole region that would have been observed, in a very short time, towards the year 1000, produced by a dismemberment of the political sovereignties). The documents of Castile and Leon indicate that changes were very slow and unequal in each place. Thus, in historical Extremadura knighthood arose from a peasant community. As regards the social condition of the Cid, we may affirm that Rodrigo Díaz, like others infanzones, served his lord within a personal bond of vassallage. Such an honorable dependence (which, nevertheless, could be interrupted) was the basis for the reception of fiefs that were then added to the own patrimony.